2016
DOI: 10.1039/c5nr05643h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ni–Co layered double hydroxide nanosheets entrapped on conductive textile fibers: a cost-effective and flexible electrode for high-performance pseudocapacitors

Abstract: Hierarchical three-dimensional (3D) porous nanonetworks of nickel-cobalt layered double hydroxide (Ni-Co LDH) nanosheets (NSs) are grown and decorated on flexible conductive textile substrate (CTs) via a simple two-electrode system based electrochemical deposition (ED) method. By applying a proper external cathodic voltage of -1.2 V for 15 min, the Ni-Co LDH NSs are densely deposited over the entire surface of the CTs with good adhesion. The flexible Ni-Co LDH NSs on CTs (Ni-Co LDH NSs/CTs) architecture with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(150 citation statements)
references
References 68 publications
6
144
0
Order By: Relevance
“…This means that the interfacial redox reactions are rapid enough under the given scan rates [19]. In addition, as plotted in the inset of Fig.…”
Section: Positive Electrode Materials (Cnp-ldh)mentioning
confidence: 80%
See 1 more Smart Citation
“…This means that the interfacial redox reactions are rapid enough under the given scan rates [19]. In addition, as plotted in the inset of Fig.…”
Section: Positive Electrode Materials (Cnp-ldh)mentioning
confidence: 80%
“…However, LDH suffers from its intrinsic low electrical conductivity and highly packed morphology, resulting in low rate performance and poor cycle life in supercapacitors [14,15]. To overcome this drawback, an effective approach is to design a binder-free electrode incorporating LDH with a conductive substrates such as conductive textile fibers [19], titanium plate [20], stainless steel [21] as well as nickel foam (NF) [22,23]. In such binder-free electrode approach, the traditional manufacture process of the slurry-derived electrode is neglected.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in inset of Fig. 9D, the CNRG/Ni(OH) 2 displays a much smaller semicircle over the high frequency range, and a more upright line than those of pure Ni(OH) 2 , implying this hybrid composite possesses faster ion diffusion process and lower charge transfer resistance during the faradic reaction63. It can be concluded that the high electronic conductivity of the CNRG/Ni(OH) 2 can be ascribed to the unique structure of CNRG with large surface area and porous feature, which can make Ni(OH) 2 nanosheets keep highly interconnected with each other to facilitate the electron transport.…”
Section: Resultsmentioning
confidence: 95%
“…Cyclic voltammetry (CV), galvanic charge-discharge (GCD) measurements and electrochemical impedance spectroscopy (EIS) were performed by using an IVIUMSTAT (The Netherlands) electrochemical interface system. The specific capacitance of the electrode materials was measured by GCD curves and can be estimated based on the following equation:25…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the carbon-based materials (such as activated carbon and graphene materials) in EDLCs and transition metal oxides/hydroxide (Co 3 O 4 , MnO 2 , NiCo 2 O 4 , Co(OH) 2 , Ni(OH) 2 , etc.) in pseudocapacitors are being extensively investigated because of their low cost, less toxicity and versatility in structure and morphology171819202122232425. Despite the significant developments achieved in electroactive materials for EDLCs and pseudocapacitors, the suitability of these materials for practical applications is still limited because of their poor specific capacitance in carbon-based materials, while the relatively low power density and poor cycling stability usually occur in transition metal oxide/hydroxides31426.…”
mentioning
confidence: 99%